Location based mobile application for muslim products in Perlis / Siti Hamizah Mahidin - Mahidin, Siti Hamizah (2021)
The awareness among Muslim community in prioritizing the Muslim product are seem to show positive increment nowadays. Thus the Muslim product are currently on the demand and very acceptable by Malaysia consumers. Therefore, Muslim consumers nowadays are so much concerned and always be aware of what they eat, drink and use. In order to support the awareness it is also important to empowering Muslim economy in order to face the current challenge. Further study needs to be conducted in order to investigate experience in identifying Muslim’s product for Muslim community. The study will figure out the potential these develop mobile Web Apps for this application as this will support the current demand. At the first stage, the research observing supermarket and minimarkets located around the Perlis area. Observations are made on several types of Muslim products. The target of this study is to provide the mobile application in facilitating the users to purchase the Muslim product. The objective of the project presented in to identify the Muslim product in Perlis, then to develop a mobile apps with GIS application with the information of Muslim product, also to test the effectiveness of mobile application with the feedback sample from the users. To achieve this objectives, this paper propose a list the Muslim product and also check supermarket and minimarket area in Perlis. As preliminary stage a set of questionnaire is developed to evaluate the current demand of Muslim product among Muslim community in Perlis. Those responds are useful to see how the apps can help Muslim’s community to case their life. In this apps can provide the mobile application in facilitating the users to purchase and Muslim product services. In this also can perform the process of location by using technology of GPS and the user can determines of actual location directly to supermarket or minimarket.